Parallel Lives: Remembering the PCF and CGT. Issue 3 (1st December 2019) - Ross, George
Abstract : Philippe Herzog and Jean-Louis Moynot were members of the top leaderships of the Parti Communiste Français (PCF) and the Confédération Générale du Travail (CGT), respectively. Each participated in and lived through the dramatic years from the 1960s through the 1980s when both organizations first supported Union de la Gauche and then turned away from it, eventually precipitating both into decline in ways that would transform eventually the French political and trade union left. The strategic shifts underlying these deep and significant changes were traumatic for those who lived through them. Herzog and Moynot have recently published memoirs detailing their experiences of this period and their political lives thereafter. Both books, in different ways, give us new and important understandings of what happened during a critical moment of change in French politics.